Analisis Literasi Lingkungan Peserta Didik: Kajian Literatur Sistematis - Novita, Regina; Olvia Rahmi, Fitri (LP2M UIN Ambon, 2025)
Environmental issues are closely related to everyday life, which require education to play a crucial role in developing students with good environmental literacy. The goal of improving environmental literacy is to prepare a younger generation to act and behave positively towards the environment. Three elements are used to measure environmental literacy: cognitive, affective, and behavioral. This study aims to systematically assess students' environmental literacy. The method used was a systematic literature review of ten relevant research articles. The results of the study indicate that environmental literacy is generally effective in improving the quality of the learning process. However, the effectiveness of environmental literacy is greatly influenced by educator readiness, learning design, and the availability of learning tools and time.